A new catalytic process for high‐efficiency synthesis of p‐xylene by methylation of toluene with CH3Br. Issue 2 (14th May 2012) - Ouyang, Qiang; Yin, Shuang‐Feng; Chen, Lang; Zhou, Xiao‐Ping; Au, Chak‐Tong
<x xml:space="preserve">Abstract</x> A new catalytic process for p‐xylene synthesis from the methylation of toluene with CH3Br was proposed. CH3Br was prepared from the catalytic bromination of natural gas (CH4), by using H2O + HBr + O2 as mediator over supported Rh catalyst. The methylation conditions were investigated using HZSM‐5 or modified HZSM‐5 catalyst. Under optimal reaction conditions, p‐xylene selectivity is up to 93%, and p‐xylene yield is more than 21% at 673 k over the Si—P modified HZSM‐5 catalyst. Compared to the processes using MeOH or dimethyl carbonate (DMC) as methylation agent, this new process is very attractive in an economic standpoint since CH4 is much cheaper than MeOH and DMC. In addition, the process has other advantages, such as mild reaction conditions, simple operation, high‐product yield, and so on. It is predicted that the process has good industrial potential for para‐xylene production. © 2012 American Institute of Chemical Engineers AIChE J, 59: 532–540, 2013